2013
DOI: 10.6061/clinics/2013(07)03
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sensitivity, motor and pain thresholds across the menstrual cycle through medium-frequency transcutaneous electrical nerve stimulation

Abstract: OBJECTIVES:The aim of this study was to identify variations in nervous thresholds in different phases of the menstrual cycle in eumenorrheic women and users of oral contraceptives.METHOD:An observational study was performed including 56 volunteers, consisting of 30 eumenorrheic women who were non-users of oral contraceptives and 26 users of oral contraceptives. An electrical stimulator was employed to assess their nervous thresholds, with pulses applied at a fixed frequency of 2,500 Hz, modulated at 50 Hz, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…The complexity of the interaction of gonadal hormones and pain processing (103) is illustrated by studies that show that oscillations in hormonal levels during the 5 phases of the menstrual cycle (menstrual, follicular, ovulatory, luteal, and premenstrual) influence experimental sensitivity to thermal pain (126) in healthy women (see Figure 6) and to experimental muscle pain in women with dysmenorrhea (127). Other studies that show that changes in pressure, electrical, and cold pain thresholds, which occur over the menstrual cycle with higher thresholds to pressure and electrical pain stimuli on day 22 and to cold on day 14, are not correlated with changes in gonadal hormones (128).…”
Section: Hypothalamic Role In Hormonal Regulation Of Brain Dysmetria mentioning
confidence: 99%
“…The complexity of the interaction of gonadal hormones and pain processing (103) is illustrated by studies that show that oscillations in hormonal levels during the 5 phases of the menstrual cycle (menstrual, follicular, ovulatory, luteal, and premenstrual) influence experimental sensitivity to thermal pain (126) in healthy women (see Figure 6) and to experimental muscle pain in women with dysmenorrhea (127). Other studies that show that changes in pressure, electrical, and cold pain thresholds, which occur over the menstrual cycle with higher thresholds to pressure and electrical pain stimuli on day 22 and to cold on day 14, are not correlated with changes in gonadal hormones (128).…”
Section: Hypothalamic Role In Hormonal Regulation Of Brain Dysmetria mentioning
confidence: 99%
“…The influence of the menstrual cycle and using oral contraceptives on the EEG alpha activity was investigated in relation to hormonal changes. Some studies demonstrated that menstrual cycle and use of the oral contraceptives could effect the nervous thresholds of women (Barbosa, Guirro & Nunes, 2013;Brötzner et al, 2014;Bazanova, Nikolenko & Barry, 2017). One of the limitations of the present study is that the menstrual cycle of the young female subjects was not evaluated.…”
Section: Discussionmentioning
confidence: 87%
“…Considering that the study only included healthy women and healthy men, a certain limitation of the study was the lack of taking into account the phase of the cycle among the studied group of women. As is known, in the second phase of the cycle, water is retained in the female body, including subcutaneous tissue, which changes the conditions for the sensitivity of the sense of touch [49,50]. In the second phase of the cycle, tactile hyperesthesia temporarily occurs.…”
Section: Discussionmentioning
confidence: 99%